An evidence-based approach towards sustainable anaesthesia - Barnard, Jane; Kudsk-Iversen, Søren (Journal of the Nuffield Department of Surgical Sciences, 2023)
Health and social care currently account for between 4-5% of UK annual emissions1. Recognising this, the NHS has set a net zero goal for direct emissions by 2040, alongside an 80% reduction goal before 20322. Net zero here refers to a balance between residual emissions and carbon offsets. To this end, trusts are exploring measures to reduce their direct emissions through changes in practice, renewable electricity generation, and energy efficiency improvements. The NHS will then offset any remaining emissions after 2040. Surgery and anaesthesia together account for 8% of the carbon footprint associated with acute trusts at present, with nearly half of this due to the use of anaesthetic vapours and gases, predominantly nitrous oxide and desflurane3. The NHS net zero panel expect 2% of its total emissions reduction will be achieved through changes to the delivery of anaesthesia4. This raises the question: what changes can be made to anaesthetic practise to achieve this goal?